Geny-markery predracpolozennosti k skorostno-silovym vidam sporta - Rogozkin, V. A.; Astratenkova, I. V.; Druzevskaja, A. M.; Fedorovskaja, O. N. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of research was to reveal and analize the polymorphism of three genes: - actinine-3, adenosine monophosphate deaminase and angiotensin transforming enzyme at representatives of speed-power kinds of sports